A autonomia do educando na pedagogia de Dewey - Armando Lourenço Filho; Samuel Mendonça (EccoS – Revista Científica)
This paper aims to comprehend how it was thought the issue of the learner’s autonomy in John Dewey’s pedagogy. Dewey had advocated the importance of educa - tion while a process endowed with purpose in itself, related to the student’s life, admit - ting as forces propelling the personal interest and previous knowledge of children. The basis of Dewey’s pedagogy consists of a practical education, based on learning by doing, enabling the student to build and rebuild the knowledge starting from concrete situa - tions. As a conclusion, we realize that the learner’s autonomy is oriented mainly by prac - tical life, therefore, the philosopher’s insistence for the school be understood as child’s life, so his education proposal is through experience and action, based on the life that usually occurs beyond the school boundaries.